Association between salivary flow and dental caries in institutionalized adolescents: Cross-sectional study - Mariana da Silva Muñoz; Natália Marcumini Pola; Paulo Roberto Grafitti Colussi; Cassiano Kuchenbecker Rösing; Francisco Wilker Mustafa Gomes Muniz (Elsevier, 2024)
Background: Brazil has a larger number of adolescent offenders, but studies evaluating their oral health are still limited. Objective: Assess the association between salivary flow and caries experience in youngsters deprived of liberty. Methodology: Sixty-eight male adolescents in conflict with the law, aged between 15 and 19 years, from a Socio-Educational Assistance Center in Brazil participated in the present study. They answered a structured questionnaire, and oral examination was performed by the Decayed, Missing, and Filled Teeth (DMFT) index. The salivary flow rate was obtained using the mechanically stimulated total saliva method. Adjusted Poisson regression was used for the association with total DMFT and its decayed component, using the salivary flow (continuous fashion) or the hyposalivation (≤1 ml/min) as independent variables. Results: Participants were divided into two groups, those who did not have any decayed teeth at the moment of the examination (n = 39) and those who had at least one decayed tooth (n = 29). Moreover, two groups were formed based on the DMFT: those who had DMFT = 0 (n = 20) and those who had DMFT≥1 (n = 48). In the multivariate analysis, hyposalivation was associated with DMFT≥1 (p = 0.048), but when the salivary flow was included, no significant association with DMFT index was identified (p = 0.178). Conversely, the presence of at least one decayed tooth was significantly associated with the salivary flow (p = 0.004), but not with hyposalivation (p = 0.091). Conclusions: Institutionalized adolescents who present hyposalivation or low salivary flow are associated with DMFT≥1 index or presence of at least one decayed tooth, respectively.